Analisis Pengaruh Kepatuhan Wajib Pajak dan Pelayanan Perpajakan Terhadap Penerimaan Pajak Bumi Bangunan Pada Badan Pendapatan Daerah Kota Tangerang - Fauziah, Hanipatul; Rahmawati, Titah (Prisani Cendekia, 2025)
This study aims to analyze the effect of taxpayer compliance and tax services on property tax revenue, both simultaneously and partially. The data collection method employed in this research was a questionnaire. The sampling technique used was purposive sampling, determined based on specific criteria. Data analysis was carried out using multiple linear regression. The sample consisted of 100 respondents who met the criteria of being property taxpayers in Tangerang City and compliant in paying taxes. The findings of this study indicate that: (1) Based on the F-test, taxpayer compliance and tax services simultaneously influence property tax revenue, with F-value > F-table (71.266 > 3.09), showing that the regression model explains the variance of the dependent variable well. (2) Based on the t-test, taxpayer compliance significantly affects property tax revenue, with a significance level of 0.001 < 0.05. (3) Based on the t-test, tax services do not affect property tax revenue, with a significance level of 0.259 > 0.05.